2020
DOI: 10.1002/fsn3.1397
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of glucose homeostasis through the PI3K/Akt signaling pathway by dietary with Agaricus blazei Murrill in STZ‐induced diabetic rats

Abstract: Agaricus blazei Murrill (ABM) is an edible fungus. This study investigated the protective role of ABM fruiting body against streptozotocin (STZ)‐induced diabetic rats. After 4 weeks of ABM supplement, glucose homeostasis was improved in diabetic rats. Quantitative real‐time and Western blot analyses suggested that ABM could promote the gene and protein expression level of insulin receptor, pyruvate dehydrogenase kinase, phospho‐kinase B, kinase B, phosphatidylinositol 3‐kinase, insulin receptor substrate 1, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Our findings showed that treatment with WEA (0.8 and 1.6 g/kg BW) induced a significant decrease in serum GLU and insulin levels, suggesting that reduction of serum GLU might not possibly be related to the reduced serum insulin levels in WEA-treated rats with NAFLD. The PI3K-Akt signaling pathway plays a potential role in the insulin signaling pathway, which is considered a key regulator of gluconeogenesis and glycogen synthesis [ 29 ]. Western blot analysis revealed that WEA administration reduced liver insulin resistance by increasing Akt phosphorylation at Ser473.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that treatment with WEA (0.8 and 1.6 g/kg BW) induced a significant decrease in serum GLU and insulin levels, suggesting that reduction of serum GLU might not possibly be related to the reduced serum insulin levels in WEA-treated rats with NAFLD. The PI3K-Akt signaling pathway plays a potential role in the insulin signaling pathway, which is considered a key regulator of gluconeogenesis and glycogen synthesis [ 29 ]. Western blot analysis revealed that WEA administration reduced liver insulin resistance by increasing Akt phosphorylation at Ser473.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics is a large‐scale research technology that uses modern analytical method to assess the creature physiological status in different conditions (Wei et al., 2020 ). The metabolic profiles reflect an individual's function state at a certain point, which is consistent with the integrality and systematicness of traditional Chinese medicine (Bao et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Binding to the ligand, EGFR forms a dimer and the phosphate of ATP transfers into the tyrosine residue. Then, different kinds of proteins bind to this phosphorylated tyrosine and signals transmit to downstream pathways, such as mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3K) pathways [ 4 , 5 ]. It is well known that EGFR plays a key role in cell proliferation, apoptosis, and migration [ 6 ].…”
Section: Introductionmentioning
confidence: 99%